Stereoselective synthesis of 2, 5-disubstituted pyrrolidines via gold-catalysed anti-Markovnikov hydroamination-initiated tandem reactions. Issue 67 (1st August 2019) - Tan, Tong-De; Chen, Yang-Bo; Yang, Ming-Yang; Wang, Jia-Le; Su, Hao-Ze; Hong, Feng-Lin; Zhou, Jin-Mei; Ye, Long-Wu
Abstract : A series of gold-catalyzed intramolecular hydroamination-initiated azidation, allylation and heteroarylation reactions enable the rapid construction of enantioenriched 2, 5-disubstituted pyrrolidines. Abstract : A series of gold-catalysed intramolecular anti-Markovnikov hydroamination-initiated azidation, allylation and heteroarylation reactions of chiral homopropargyl sulfonamides have been developed. Various enantioenriched 2, 5-disubstituted pyrrolidines are obtained in moderate to excellent yields with excellent enantioselectivities and generally high diastereoselectivities.